2022
DOI: 10.24251/hicss.2022.315
|View full text |Cite
|
Sign up to set email alerts
|

Open Government Data Use by the Public Sector - an Overview of its Benefits, Barriers, Drivers, and Enablers

Abstract: Although governments publish large amounts of open data, their use by the public sector is still in its infancy. Therefore, this study aims to gain insights into promoted benefits and factors that hinder (barriers), facilitate (enablers), and propel (drivers) Open Government Data (OGD) use and reuse by the public sector. A systematic literature review of 38 publications resulted in an overview of these factors. Findings suggest that OGD use benefits are increased transparency and the development of new/improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(60 citation statements)
references
References 31 publications
0
57
0
Order By: Relevance
“…This study builds on and expands on previous works. Categories of data used, OGD uses, benefits, barriers, enablers, and drivers were distilled from our literature review reported in [ 35 ]. Moreover, the questionnaire’s complete results were published in [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…This study builds on and expands on previous works. Categories of data used, OGD uses, benefits, barriers, enablers, and drivers were distilled from our literature review reported in [ 35 ]. Moreover, the questionnaire’s complete results were published in [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to the Organization for Economic Co‐operation and Development (OECD), OGD promotes transparency, accountability, and value creation by making government data accessible to all, encouraging business innovation and citizen‐centric services. Numerous studies have highlighted OGD's potential for driving data‐driven economic development and improving public services (Herala et al, 2018; Kawashita et al, 2022; Magalhaes & Roseira, 2020; Pereira et al, 2017). In Taiwan, the government actively promotes OGD utilization, leading to various applications in different industries.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the acknowledged potential value of OGD for society, several barriers hinder the use thereof. These barriers include; the cost to access information, lack of technical skills, inability to interact with service providers and the culture of not using open data (Kawashita et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Open government data has been defined as a philosophy and, increasingly, a set of policies promoting transparency, accountability and value creation by making government data available to all (Kawashita et al, 2022; OECD, 2019). Governments around the world make their data available to the public with the aim of benefiting (Dawes et al, 2016) and providing ICT tools to enable citizens to access government information more easily (Al‐Kubaisi, 2018).…”
Section: Introductionmentioning
confidence: 99%